Thank you for the opportunity to help you with your question!
hi, I would love to answer your question, do you mind to type it out and post it again? Thank you
Is better if you help me with this one,
(Sec x - csc x )/(sec x + csc x ) = (tan x-1/ tan x+1)
so you want me to prove it right? Also is it tan(x-1) or tanx-1?
secx-cscx=1/cosx - 1/sinx=(sinx-cosx)/(cosx*sinx)
so (Sec x - csc x )/(sec x + csc x ) =(sinx-cosx)/(sinx+cosx)
(tanx-1)/(tanx+1)=(sinx/cosx - 1)/(sinx/cosx +1)=(sinx-cosx)/cosx / (sinx+cosx)/cosx=（sinx-cosx)/(sinx+cosx)
What are you trying to prove here?
Do not worry I have it
Content will be erased after question is completed.
Enter the email address associated with your account, and we will email you a link to reset your password.
Forgot your password?